Building a Disaster-Aware Young Generation Through Training and Simulation Programs - Zitri, Ilham; Subandi, Azwar; Rifaid, Rifaid; Lestanata, Yudhi; Hidayati, Hidayati; Muhammad, Rio Eza Nur (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2025)
Natural disasters are an ever-present threat with the potential to cause significant losses, both in terms of material and human loss. Given the magnitude of their impact, young people need to be equipped with awareness, knowledge, and skills to deal with potential disasters. This community service activity aims to foster youth awareness of disaster management through training and simulation programs. Implementation methods include education on disaster types, field practice, and disaster management simulations involving youth communities in disaster-prone areas. Results of the activity demonstrated a significant increase in participants' understanding of mitigation procedures, self-rescue techniques, and coordination during disasters. In addition to cognitive aspects, this activity also fostered responsiveness, discipline, social awareness, and solidarity among young people. Thus, training and simulations have proven effective as educational strategies for building preparedness and producing a caring, resilient, and adaptive young generation in the face of disaster risks.